PERANAN INFLUENCER TRAVEL DALAM PEMASARAN DAYA TARIK WISATA PADA DESTINASI MANDALIKA, LOMBOK - Rinto Wardito,; Isdar Wahim,; I.A.Y.S.D Utami Pidada, (Juremi: Jurnal Riset Ekonomi, 2024)
Tourism destinations today increasingly the influence of travel influencers in promoting their attractions. This research aims to explore the role that travel influencers play in destination marketing, focusing on the case of Mandalika Destination in Lombok. Through literature analysis, this article presents an in-depth understanding of how travel influencers influence tourists' perception and interest in the destination, as well as the strategies used to increase Mandalika's visibility and appeal through social media platforms. The findings of this study highlight the importance of cooperation between tourism destinations and travel influencers, as well as its practical implications in developing effective marketing strategies to increase tourist visits and boost local economic revenue. This research makes an important contribution in the context of modern tourism marketing, by providing insights into how the utilization of travel influencers can be an effective tool in promoting and marketing tourism destinations